Analysis of symbolism reflecting the theme of death in the film "The Undertaker" - Taiphrom, Sarocha; Padthum, Anchuleepron; Sakorn, Preecha; Lata, Siriwiwat (Journal for Developing the Social and Community, 2026)
Background and Aims: This research, titled "An Analysis of Symbolism Reflecting the Concept of Death in the Film the Undertaker," examines the film’s narrative architecture and the symbolic layers embedded within its portrayal of mortality. The study explores how the cinematic medium serves as a vehicle for articulating social and philosophical perspectives on life and death, specifically within the cultural landscape of Northeastern Thailand (Isan) and broader Thai society. Methodology: This qualitative study draws on Storytelling Theory and Semiology as its primary analytical frameworks. The research process involved a close reading of the film’s visual compositions, supplemented by a review of relevant academic literature. To deepen the analysis, in-depth interviews were conducted with the director, providing direct insight into the conceptual intent and the symbolic logic used throughout the film. This multi-faceted approach ensures a nuanced understanding of the work. Results: The findings indicate that The Undertaker employs a parallel narrative structure-centered on the characters "Jerd" and "Xiang"- to mirror diverse human responses to death, ranging from existential dread and attachment to ultimate acceptance. This progression aligns with Gustav Freytag’s dramatic arc, tracing the characters' psychological evolution toward the realization that death is an intrinsic facet of existence. Both the semiotic analysis and directorial insights reveal a deliberate use of characterization, mise-en-scène, lighting, and local funerary rites-such as coffin tapping, the ritual binding of the deceased, and the traditional egg-tossing ceremony-to convey Buddhist tenets of detachment and the cyclical nature of life. Conclusion: The study concludes that The Undertaker transcends conventional entertainment, functioning as a vital cultural site that articulates profound ontological views on mortality. By seamlessly weaving Isan traditions into the fabric of contemporary Thai values, the film recontextualizes death not as a finality, but as a natural transition within the broader continuum of life.